2021
DOI: 10.1109/access.2021.3054887
|View full text |Cite
|
Sign up to set email alerts
|

A Security Analysis of Blockchain-Based Did Services

Abstract: Decentralized identifiers (DID) has shown great potential for sharing user identities across different domains and services without compromising user privacy. DID is designed to enable the minimum disclosure of the proof from a user's credentials on a need-to-know basis with a contextualized delegation. At first glance, DID appears to be well-suited for this purpose. However, the overall security of DID has not been thoroughly examined. In this paper, we systemically explore key components of DID systems and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Many DID frameworks are built on top of a blockchain [86]. Indeed, DID preserves users' privacy while promoting a universally unique identity that can be used across multiple blockchains [87]. Currently, the DID framework is being considered for universal standardization by the World Wide Web Consortium (W3C) [88] which implies the importance of integrating it with the current blockchain-based UAV networks.…”
Section: A Multiple Uav Service Suppliersmentioning
confidence: 99%
“…Many DID frameworks are built on top of a blockchain [86]. Indeed, DID preserves users' privacy while promoting a universally unique identity that can be used across multiple blockchains [87]. Currently, the DID framework is being considered for universal standardization by the World Wide Web Consortium (W3C) [88] which implies the importance of integrating it with the current blockchain-based UAV networks.…”
Section: A Multiple Uav Service Suppliersmentioning
confidence: 99%
“…There are three popular federated identity protocols available: SAML, OAuth, and OpenID since 2005. Using protocols like OpenID Connect, social login buttons from Facebook, Google, Twitter, LinkedIn, etc., are now a standard feature on many consumer-facing websites [8,9].…”
Section: Digital Identity Management Systemmentioning
confidence: 99%
“…uPort, ShoCard, BitID, and soverin are examples of decentralised identity models. Further, the self-sovereign identity (SSI) model is a decentralised model that facilitates the recording and exchange of identity attributes and the propagation of trust among participating entities [9,10].…”
Section: Digital Identity Management Systemmentioning
confidence: 99%
“…Users' privacy is one of these systems' properties. Kim et al [12] systemically explored key components of DID systems and analyzed their possible vulnerabilities when deployed. Liu et al [13] showed different self-sovereign open-source identity management systems provided to users, organizations, and other entities.…”
Section: Related Workmentioning
confidence: 99%